Interplay between OmpA and RpoN Regulates Flagellar Synthesis in Stenotrophomonas maltophilia - Liao, Chun-Hsing (Microorganisms, 2021)
OmpA, which encodes outer membrane protein A (OmpA), is the most abundant transcript in Stenotrophomonas maltophilia based on transcriptome analyses. The functions of OmpA, including adhesion, biofilm formation, drug resistance, and immune response targets, have been reported in some microorganisms, but few functions are known in S. maltophilia. This study aimed to elucidate the relationship between OmpA and swimming motility in S. maltophilia. KJΔOmpA, an ompA mutant, displayed compromised swimming and failure of conjugation-mediated plasmid transportation. The hierarchical organization of flagella synthesis genes in S. maltophilia was established by referencing the Pseudomonas aeruginosa model and was confirmed using mutant construction, qRT-PCR, and functional assays. Distinct from the P. aeruginosa model, rpoN, rather than fleQ and fliA, was at the top of the flagellar regulatory cascade in S. maltophilia. To elucidate the underlying mechanism responsible for ΔompA-mediated swimming compromise, transcriptome analysis of KJ and KJΔOmpA was performed and revealed rpoN downregulation in KJΔOmpA as the key element. The involvement of rpoN in ΔompA-mediated swimming compromise was verified using rpoN complementation, qRT-PCR, and function assays. Collectively, OmpA, which contributes to bacterial conjugation and swimming, is a promising target for adjuvant design in S. maltophilia.